Ground Improvement Techniques and Geosynthetics IGC 2016 Volume 2 - Thyagaraj, T. (Lecture Notes in Civil Engineering,, 2019)
The book comprises select proceedings of the 2016 annual conference of the Indian Geotechnical Society (IGC 2016), with technical papers on the theme "Ground Improvement and Geosynthetics". The papers cover a wide range of topics, including chemical modification using admixtures, microbial-induced carbonate precipitation, geopolymers, fly ash and other industrial wastes, modification using geosynthetic materials such as natural and synthetic fibers, expanded polystyrene (EPS) geofoam, prefabricated vertical drains, geosynthetic encased-granular columns and mechanical densification through sand columns. This book is a valuable reference for researchers and practicing engineers alike.